Inflamma-miRs in Aging and Breast Cancer: Are They Reliable Players? - Cătană, Cristina Sorina; Calin, George A.; Berindan-Neagoe, Ioana (Frontiers in Medicine, 2015)
Human aging is characterized by chronic low-grade inflammation known as “inflammaging.” Persistent low-level inflammation also plays a key role in all stages of breast cancer since “inflammaging” is the potential link between cancer and aging through NF-kB pathways highly influenced by specific miRs. Micro-RNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at a post-transcriptional level. Inflamma-miRs have been implicated in the regulation of immune and inflammatory responses. Their abnormal expression contributes to the chronic pro-inflammatory status documented in normal aging and major age-related diseases (ARDs), inflammaging being a significant mortality risk factor in both cases. Nevertheless, the correct diagnosis of inflammaging is difficult to make and its hidden contribution to negative health outcomes remains unknown. This methodological work flow was aimed at defining crucial unanswered questions about inflammaging that can be used to clarify aging-related miRNAs in serum and cell lines as well as their targets, thus confirming their role in aging and breast cancer tumorigenesis. Moreover, we aim to highlight the links between the pro-inflammatory mechanism underlying the cancer and aging processes and the precise function of certain miRNAs in cellular senescence (CS). In addition, miRNAs and cancer genes represent the basis for new therapeutic findings indicating that both cancer and ARDs genes are possible candidates involved in CS and vice versa. Our goal is to obtain a focused review which could facilitate future approaches in the investigation of the mechanisms by which miRNAs control the aging process by acting as efficient ARDs inflammatory biomarkers. An understanding of the sources and modulation of inflamma-miRs, along with the identification of their specific target genes could enhance their therapeutic potential.